Oral administration of clabet (Trigonella foenum graecum) seeds ethanol extracts improved testosteron level in old-male wistar (Rattus norvegicus) mice - Bissi Herliane; Wimpie Pangkahila; IGM Aman (Fakultas Kedokteran Universitas Udayana, 2018)
Introduction: Aging can cause decreased testosterone levels in men which is known as andropause. Some herbs are known to increase the levels Testosterone. One of them is Klabet seed that contain phyto-testosterone. The purpose of this study was to prove that the administration of ethanol extract of Klabet seeds increased testosterone levels in old male Wistar rats. Methods: A pretest-posttest control group design study was conducted using 20 male white wistar rats that were divided into 2 (two) groups: control group that received 2 cc of distilled water and treatment group that received 2 cc ethanol extract of Klabet seeds 250mg/250gBB rats/day by sonde for 14 days. The testosterone level was measured on day 1 and 15. Results: The analysis showed that there was no significant difference in the pre-test and post-test testosterone level P0 (Pre-test:16.4±0.553 ng/ml; posttest: 15.9±1.51ng/ml) while increased level of testosterone could be observed in treatment group (P1) (pre-test: 16.6±0.476ng/ml; post-test: 19.4±0.828ng/ml. Comparative analysis between post-test results (P0 vs P1) showed that the difference was statistically significant (p <0.001). Conclusion: Oral administration of Klabet seeds ethanol extract can significantly increase testosterone level in old male wistar mice.